A study of attitudes of colostomy patients towards a stoma - S. G. Majola; B. B. Ntombela; B. M. Zungu (AOSIS, 1995)
The researcher experienced that colostomy patients in the community are overprotected by their family members who viewed them as sick persons and do not permit them to continue with their household chores and daily activities. The patients are also stigmatised and labelled and this hurts and humiliates them especially if one has to shout in public about them. The colostomy patients are withdrawn, depressed and lonely.